Reinforcing effects of synthetic cathinones in rhesus monkeys: Dose-response and behavioral economic analyses - de Moura, Fernando B.; Sherwood, Alexander; Prisinzano, Thomas E.; Paronis, Carol A.; Bergman, Jack; Kohut, Stephen J. (Pharmacology, biochemistry and behavior, 2021)
The abuse of synthetic cathinones (“bath salts”) with psychomotor stimulant and/or entactogenic properties emerged as a public health concern when they were introduced as “legal” alternatives to drugs of abuse such as cocaine or MDMA. In this study, experiments were conducted in nonhuman primates to examine how differences in transporter selectivity might impact the reinforcing effects of synthetic cathinones. Rhesus monkeys (N = 5) were trained to respond for intravenous injections under a fixed-ratio (FR) 30, timeout 60-s schedule of reinforcement. The reinforcing effects of selected cathinones (e.g., MDPV, αPVP, MCAT, and methylone) with a range of pharmacological effects at dopamine and serotonin transporters were compared to cocaine and MDMA using dose-response analysis under a simple FR schedule and behavioral economic procedures that generated demand curves for two doses of each drug. Results show that one or more doses of all drugs were readily self-administered in each subject and, excepting MDMA (21 injections/session), peak levels of self-administration were similar across drugs (between 30 and 40 injections/session). Demand elasticity for the peak and the peak + 1/2-log dose of each drug did not significantly differ, and when data for the two doses were averaged for each drug, the following rank-order of reinforcing strength emerged: cocaine > MCAT = MDPV = methylone > αPVP = MDMA. These results indicate that the reinforcing strength of synthetic cathinones are not related to their selectivity in binding dopamine or serotonin transporter sites. •Synthetic cathinones maintain self-administration behavior in nonhuman primates.•Reinforcing strength of synthetic cathinones does not appear to be related to selectivity for dopamine vs. serotonin.•Illicit use of synthetic cathinones is most likely attributable to their dopaminergically-mediated actions.